Implementation of Fuzzy Logic in Determining Recommendations for Purchasing Folic Acid Supplements based on Fruit and Vegetable Consumption Patterns in Pregnant Mothers - Annisa Nurul Adelia; Al Zahra Dwi Pranata Lia Tanjung; Jesika Azura; Windy Anjeli Br Sitanggang; Sophia Solihati Devi; Syifa Hawasiatul Fikriyah; Myita Syabrina; Shafira Az-zahra; Ardya Hadi Kusuma; Muhammad Arsyad Budiman; Muhammad Danang Mukti Darmawan; Nanda Octavia; Ester Angeline; Fiqri Nurfadillah; Mrr. Lukie Trianawati (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
This research aims to implement fuzzy logic in determining the level of recommendation for folic acid supplements based on the input of the amount of vegetable and fruit consumption and folic acid content. The output of the developed system is in the form of recommendation level with categories of "not recommended", "less recommended", and "recommended". This research data was obtained based on literature studies and through observation of samples of supplements containing folic acid in several related pharmacies. This research method includes direct calculations and the use of MATLAB. The results show that in the example case with the amount of vegetable and fruit consumption of 550 with a folic acid content of 175 can produce an output value of 400 which puts the recommendation level based on dosage in the "not recommended" position. This result has been verified both through direct calculation and the use of MATLAB software. Studies have concluded that the application of using of fuzzy logic can help in providing supplement levels. This contributes to considerate of decision-making in the community, especially in pregnant women, which can help determine the supplements consumed so that the fulfillment of daily consumption of folic acid content can be met.